2018
DOI: 10.1016/j.soilbio.2018.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Spatial zoning of microbial functions and plant-soil nitrogen dynamics across a riparian area in an extensively grazed livestock system

Abstract: Anthropogenic activities have significantly altered global biogeochemical nitrogen (N) cycling leading to major environmental problems such as freshwater eutrophication, biodiversity loss and enhanced greenhouse gas emissions. The soils in the riparian interface between terrestrial and aquatic ecosystems may prevent excess N from entering freshwaters (e.g. via plant uptake, microbial transformations and denitrification). Although these processes are well documented in intensively managed agroecosystems, our un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 76 publications
(58 reference statements)
1
6
0
Order By: Relevance
“…In contrast, studies conducted in natural or semi-natural habitat conditions such as grassland, forests, and woodlands, showed no significant changes between riparian zones and adjacent fields or upland forests [45,[46][47][48]. Moreover, some studies have indicated that soil nutrient content increased significantly with distance to the river [49][50][51]. Our own data support these findings when analyzing TC, TOC, TN, and A-P.…”
Section: Response Of Soil Nutrients To Lateral Distance Of Riparian Zonesupporting
confidence: 73%
See 1 more Smart Citation
“…In contrast, studies conducted in natural or semi-natural habitat conditions such as grassland, forests, and woodlands, showed no significant changes between riparian zones and adjacent fields or upland forests [45,[46][47][48]. Moreover, some studies have indicated that soil nutrient content increased significantly with distance to the river [49][50][51]. Our own data support these findings when analyzing TC, TOC, TN, and A-P.…”
Section: Response Of Soil Nutrients To Lateral Distance Of Riparian Zonesupporting
confidence: 73%
“…On the one hand, flood regimes impose stress and disturbance on riparian plants and soils near the river and redistribute sediment and organic matter. This can cause gradient distribution of plants and soils along the lateral distance of the riparian zone, according to flooding tolerance of riparian plants and deposition process of sediments, respectively [34,51]. On the other hand, riparian plant species diversity is higher in areas with groundwater discharge because of the higher nutrient availability [4,12].…”
Section: Relationship Between Soil Nutrients and Plant Species Diversmentioning
confidence: 99%
“…Whilst riparian wetlands have been shown to act as biogeochemical cycling hotspots, with the potential to transform and attenuate the nutrient and geochemistry signal from the catchment as it moves from land to water [1,3,[17][18][19], the efficacy of this function in real terms is controlled by the specific distribution of functional zones or biogeochemical cycling hotspots within the wetland. These in turn are controlled by the chemical character and distribution of contributing source areas of flow to the wetland between and within a water year, flow routing through the wetland, the residence time of water within the wetland and contact or exposure time between the microbial community and the nutrient parcel transitioning through the wetland; while soil organic carbon content and dissolved organic matter in porewaters acts as an energy resource to support denitrification, with redox status varying laterally, vertically and over time [7,11,20,21]. Reported denitrification rates vary widely within and between riparian wetlands, and over time, with annual rates reported to vary from <3 kg N ha −1 to >500 kg N ha −1 in denitrification hotspots in wet meadow systems, and <4 kg N ha −1 to >65 kg N ha −1 in riparian forests [22].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies show that denitrification rates increase with increasing soil moisture (Burgin et al, 2010) and carbon concentrations (Groffman and Crawford, 2003;Xiong et al, 2017), root biomass (Gift et al, 2010) and plant species richness (Xiong et al, 2017;Ye et al, 2017), and positively correlate with increased abundance of key denitrification genes: nirS, nirK and nosZ (Tatariw et al, 2013;Rocca et al, 2015;Xiong et al, 2017;de Sosa et al, 2018b). However, other studies report that denitrification rates are not correlated with denitrifier abundance (Dandie et al, 2008;Henderson et al, 2010) and are highly variable depending on local conditions, i.e., season (Burgin et al, 2010;Tomasek et al, 2017).…”
Section: Introductionmentioning
confidence: 99%